Public versus private wage differential in Brazilian public firms - Andre Mancha; Enlinson Mattos (EconomiA, 2020)
This work explores that Brazilian public firms were allowed to hire workers either as statutory ("civil servants") as well as under private market labor regime ("CLT"). We use RAIS that matches employer-employee data for all formal firms in Brazil from 2014 to 2016 to control for fixed effects at the individual and firm levels and the Oaxaca-Blinder decomposition to quantify the size of the wage differential explained by the labor regime versus individual characteristics. We find that CLT civil servants earn in average R 310.00 per month less than similar statutory positions, a difference of 13% comparing the average wage of each group. Only for high skilled workers we found a salary R 95.98 larger for CLT employees. Last, our decomposition strategy reveals that the largest share of the gap is not explained by endowments differences.
Keywords: C23; H50; J31; 330; Wage; Differential; Civil; Servants; Public; Versus; Private; Employers; Brazilian; Firms